2021
DOI: 10.1108/jarhe-09-2020-0287
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the emotional intelligence of school principals and the impact on school climate in public schools in the United Arab Emirates

Abstract: PurposeAt this juncture, one needs to analyze the problem statement and the purpose of this article. It is an undeniable fact that the schools are no longer classroom-oriented teaching but demands a higher level of teaching that will help students enhance their maximum potential. Having instructional based knowledge, knowledge of policies both in national and regional level and implementing them on time is not adequate for their success. Research in this area has prompted academicians to delve further into fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
4
0
5
Order By: Relevance
“…Additionally, there is a positive relationship between emotional intelligence and cooperative work skills indicating that principals with higher EI exhibit better collaborative work practices (Fakhrou, Moarbes, Rjeily, & Essa, 2022). However, it is significant to highlight that research has indicated insufficient emotional intelligence among principals in different fields which may have detrimental effects on the educational environment (Al Shehhi, Alzouebi, & Ankit, 2020 ). It is recommended that emotional intelligence skills be incorporated into the recruitment process and that professional development programs be implemented to enhance principals' emotional intelligence to improve their performance (Chukwunonso, Mary, & Patrick, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, there is a positive relationship between emotional intelligence and cooperative work skills indicating that principals with higher EI exhibit better collaborative work practices (Fakhrou, Moarbes, Rjeily, & Essa, 2022). However, it is significant to highlight that research has indicated insufficient emotional intelligence among principals in different fields which may have detrimental effects on the educational environment (Al Shehhi, Alzouebi, & Ankit, 2020 ). It is recommended that emotional intelligence skills be incorporated into the recruitment process and that professional development programs be implemented to enhance principals' emotional intelligence to improve their performance (Chukwunonso, Mary, & Patrick, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…En virtud de ello, deben estar bien cualificados y capacitados para tratar con las diferentes emociones de los docentes y así liderar el cambio de forma eficaz (Al Shehhi et al, 2021) y apoyar a los docentes en el trabajo diario que realizan (Sánchez et al, 2020). Del mismo modo, la revisión sugiere que las acciones de liderazgo del director predicen el clima escolar y, en conjunto, la mejora general del centro (McCarley et al, 2016).…”
Section: Perspectivas Teóricas Del Liderazgo Directivo Y Clima Organi...unclassified
“…, 2021; Halimi et al. , 2021), and affects students' learning and teachers' performance (Al Shehhi et al. , 2021; Wang, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Emotional intelligence refers to people's perceived emotional abilities and skills (Chittiprolu et al, 2021;Halimi et al, 2021), and affects students' learning and teachers' performance (Al Shehhi et al, 2021;Wang, 2019). From this perspective, learning readiness can be both a contributing and limiting factor in professional culinary learning (Askren and James, 2021;Kokkranikal and Carabelli, 2021).…”
Section: The Emotional Intelligence Perspectivementioning
confidence: 99%